Effectiveness of Nutrition Education on Anemia on the Level of Knowledge in Adolescents Girls - Anik Sulistiyanti; Silvi Mutia Ayu; Yuni Puji Widiastuti; Carlos Filipe da Costa Nunes (Global Health Science Group, 2022)
Anemia is a condition in humans with a decrease in the amount of hemoglobin in red blood cells that is insufficient to meet physiological needs and reduce oxygen levels in the blood. Lack of knowledge about nutrition is one of the most significant reasons for nutritional problems and consequently improper nutrition practices can lead to various complications that occur such as anemia. The purpose of this study was to determine the effect of nutrition education on anemia on the level of knowledge of adolescent girls in Masaran village, Sragen.This study uses a True experimental research design with Pretest and Posttest Control Group Design. The population is all young women in the Masaran Village, Sragen with a sample technique using purposive sampling, totaling 40 respondents. Data analysis using Univariate analysis and Bivariate analysis using t-test. Based on the average value of knowledge in the control group was 63.75 and the average value of knowledge in the intervention group was 85.50. Bivariate analysis with statistical test results using the t-test was carried out, the results obtained p value of 0.000.This study has the effect of differences in knowledge about anemia in adolescent girls before and after being given anemia nutrition education.